Hypoxia-responsive nanomaterials for tumor imaging and therapy - Xia, Yifei; Duan, Shao; Han, Chaozhe; Jing, Chengwei; Xiao, Zunyu; Li, Chao (Frontiers in Oncology, 2022)
Hypoxia is an important component of tumor microenvironment and plays a pivotal role in cancer progression. With the distinctive physiochemical properties and biological effects, various nanoparticles targeting hypoxia had raised great interest in cancer imaging, drug delivery and gene therapy during the last decade. In the current review, we provided a comprehensive view on the latest progress of novel stimuli-responsive nanomaterials targeting hypoxia-tumor microenvironment (TME), and their applications in cancer diagnosis and therapy. Future prospect and challenges of nanomaterials are also discussed.